RENDEMEN TEPUNG BUAH NIPAH (Nyfa fruticans WURMB) BERDASARKAN JARAK TEMPAT TUMBUH - Fatriani Fatriani; Noor Mirad Sari; Muhammad Noor Mashudi (Jurnal Hutan Tropis, 2011)
Abstract.  This study aims to determine the magnitude of the yield of wheat grown fruit Nipah by site. Nipah fruit yield of flour was 27.69% submerged in water, slightly submerged in water is 25.00% and grown on land which is 24.73%, Based on the analysis of the growing diversity was no significant effect on the yield of the resulting flour. Factors that influence the magnitude of the yield of fruit flour Nipah is the raw material used, Nipah fruit size, equipment used in the production process, and rigor in the process of flour production Nipah fruit. Based on the results obtained it is necessary to study Nipah fruit yield of flour from various regions, with special techniques and tools in the fruit paring Nipah.Keywords: Nipah, starch, sucrose contentABSTRAK.  Penelitian ini bertujuan untuk mengetahui besarnya rendemen  tepung buah Nipah berdasarkan tempat tumbuh. Rendemen tepung buah Nipah yang terendam air adalah 27,69% ,yang agak terendam air adalah 25,00% dan yang tumbuh di daratan  adalah 24,73%, Berdasarkan analisis keragaman ternyata tempat tumbuh tidak memberikan pengaruh yang nyata terhadap rendemen tepung yang dihasilkan. Faktor-faktor yang mempengaruhi besarnya rendemen tepung buah Nipah adalah bahan baku yang digunakan, ukuran buah Nipah, peralatan yang digunakan dalam proses produksi, dan ketelitian dalam proses produksi tepung buah Nipah. Berdasarkan hasil yang diperoleh maka perlu penelitian rendemen tepung buah Nipah dari berbagai daerah,  dengan teknik dan alat khusus dalam pengupasan buah Nipah.Katakunci : Nipah, tepung, rendemen